Next-Generation Sequencing Reveals High Uncommon EGFR Mutations and Tumour Mutation Burden in a Subgroup of Lung Cancer Patients - Guo, Gang; Li, Gaofeng; Liu, Yinqiang; Li, Heng; Guo, Qi; Liu, Jun; Yang, Xiumei; Shou, Tao; Shi, Yunfei (Frontiers in Oncology, 2021)
Xuanwei County in Southwest China shows the highest incidence and mortality rate of lung cancer in China. Although studies have reported distinct clinical characteristics of patients from Xuanwei, the molecular features of these patients with non-small cell lung cancer (NSCLC) remain unclear. Here, we comprehensively characterised such cases using next-generation sequencing (NGS). Formalin-fixed, paraffin-embedded tumour samples from 146 patients from Xuanwei with NSCLC were collected for an NGS-based target panel assay; their features were compared with those of reference Chinese and The Cancer Genome Atlas (TCGA) cohorts. Uncommon EGFR mutations, defined as mutations other than L858R, exon 19del, exon 20ins, and T790M, were the predominant type of EGFR mutations in the Xuanwei cohort. Patients harbouring uncommon EGFR mutations were more likely to have a family history of cancer (p = 0.048). A higher frequency of KRAS mutations and lower frequency of rearrangement alterations were observed in the Xuanwei cohort (p < 0.001). Patients from Xuanwei showed a significantly higher tumour mutation burden than the reference Chinese and TCGA cohorts (p < 0.001). Our data indicates that patients from Xuanwei with NSCLC harbouring G719X/S768I co-mutations may benefit from treatment with EGFR-tyrosine kinase inhibitors. Our comprehensive molecular profiling revealed unique genomic features of patients from Xuanwei with NSCLC, highlighting the potential for improvement in targeted therapy and immunotherapy.